Sistemas de plantio no manejo de plantas daninhas e na comunidade microbiana do solo na cultura do pimentão - Cunha, Jorge Luiz Xavier Lins (2012)
Three experiments aimed to evaluate the interference and the population dynamics of weeds, the soil microbial community in sweet pepper cultivation in the no-tillage (NT) and conventional planting systems (CPS) were accomplished in the didactics garden of Universidade Federal Rural do Semi-Árido (UFERSA), in the city of Mossoró-RN. In the first experiment, the period before interference (PBI), the total period of interference prevention (TPIP) and critical period of interference prevention (CPIP) of weeds in sweet pepper grown in no-tillage and conventional planting system were evaluated. In each planting system, six periods of control and coexistence of weed and sweet pepper cultivation were evaluated [0, 0-14, 0-49, 0-70, 0-91 and 0-112 days after transplanting (DAT)]. The weed interference reduced the number of fruits per plant, fruit size and sweet pepper yield in both systems. The CPIP was 19-95 - DAT at the no-tillage planting system and from 11 to 100 DAT in conventional planting system. The highest productivity of sweet pepper was found in the NT in relation to the CPS. In the second experiment, the microbial community in the soil cultivated with sweet peppers grown in no-tillage and conventional plating systems associated with weed management strategies (covering the soil with black polyethylene film, with regular and no weeding) were evaluated. The evaluations occurred in five periods: at 21, 42, 63, 84 and 105 DAT, in which soil microbial communities were quantified (fungi, bacteria and actinomycetes). The microbial community varied throughout the cultivation cycle, being influenced by the planting systems and by weed management, with the largest population of bacteria, and fungi actinomycetes in soil covered with mulch in no-tillage or with weed in both planting systems. The soil coverage with polyethylene film and bare soil provided higher rise in temperature, creating unfavorable conditions to the development of microorganisms. In the third experiment, a phytosociological study of weeds in areas cultivated with sweet pepper in no-tillage and conventional planting systems were performed. For each planting system, at 60 DAT, 32 samples with hollow square of 0.25 m² were collected. The following characteristics were evaluated: density, frequency, abundance, relative density, relative frequency, relative abundance, relative dry mass, and index of relative importance value. In the cultivated area in the CPS, 18 weed species have been identified with density of 466.5 plants